Curricular changes in social studies in the Philippines elementary school from 1900 to 1960 - Gensaya, Felipe Gestosani 1922- (s.n.], 1967)
This study traced the changes in social studies offerings in Philippine public elementary schools for the period of sixty years. The span of time beginning from the American occupation in 1900 to 1960, is divided into four historical periods, namely: the American occupation, 1900-1935; the Commonwealth period, 1935-1946; the Japanese occupation, 1942-1945; and the Republic Era, 1946-1960.